2019
DOI: 10.1111/head.13723
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Acupuncture vs Standard Pharmacological Therapy for Migraine Prevention

Abstract: Background.-Standard pharmacological treatment of migraine has many shortcomings. Acupuncture is becoming a more widely used therapy for the prevention and treatment of migraine, but its effectiveness is still in question when compared to the pharmacological treatments even though very few of these have Class A and B evidence for migraine prevention. This is a systematic review of data from existing randomized trials that compare the effectiveness of acupuncture treatment with conventional migraine preventativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…However, the nding might, on the other hand, re ect the true effect of acupuncture in practice. Several trials testing the effect of acupuncture on episodic migraine also showed superiority of acupuncture over standard pharmacological treatments [47][48][49], and one of our SRs comparing acupuncture with propranolol using indirect evidence also showed similar results [50]. Based on these grounds, a new trial on chronic migraine with larger sample size might also showed similar results.…”
Section: Discussionsupporting
confidence: 55%
“…However, the nding might, on the other hand, re ect the true effect of acupuncture in practice. Several trials testing the effect of acupuncture on episodic migraine also showed superiority of acupuncture over standard pharmacological treatments [47][48][49], and one of our SRs comparing acupuncture with propranolol using indirect evidence also showed similar results [50]. Based on these grounds, a new trial on chronic migraine with larger sample size might also showed similar results.…”
Section: Discussionsupporting
confidence: 55%
“…However, methodological heterogeneity precludes aggregation of these data and impacts comparison among studies [9][10]. Six previous studies compared acupuncture with pharmacological treatments in episodic migraine [11][12][13][14][15][16]. In the rst randomized study 85 patients, with migraine with and without aura, were allocated to a 17-week regimen either with acupuncture and placebo tablets or to placebo stimulation and metoprolol 100 mg daily: both group exhibited a reduction in attack frequency while metoprolol group showed a lower global rating of attacks [11].…”
Section: Discussionmentioning
confidence: 99%
“…A large corpus of evidence has reported encouraging results for acupuncture as a prophylaxis therapy of migraine [8][9][10]. However, trails investigated the e cacy of acupuncture in comparison to pharmacological treatment in episodic migraine showed con icting results, mainly due to differences in population characteristics, study design and outcome measures [10][11][12][13][14][15][16]. Moreover, the majority of these studies compared acupuncture with monotherapy as prophylactic treatment and ndings comparing acupuncture with the best medical treatment are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention: 20 acupuncture sessions vs. non-penetrative sham acupuncture When compared to sham acupuncture, the 20-session acupuncture treatment yielded statistically significant differences in reducing migraine frequency (week 17–20) and duration (week 13–20) This multicentered, randomized controlled clinical trial provides support for acupuncture treatment as an effective alternative treatment for patients with episodic migraines without aura. A limitation of the study is the lack of information on baseline drug prophylaxis on each patient Zhang et al (2020) [ 58 ] 7 RCTs on patients with migraines (± aura) comparing acupuncture to standard migraine prophylaxis Several studies (4/7) showed statistically significant superiority of acupuncture over drug therapy The authors comment how the heterogeneity and variability (e.g., acupuncture protocol, lack of management standardization) across the studies made it difficult to definitely endorse acupuncture; however, there is growing evidence showing the effectiveness and safety of acupuncture for migraine prophylaxis Li et al (2019) [ 56 ] 13 RCTs ( n = 1559 patients) comparing electroacupuncture (EA) to various control methods (e.g., Western medicine, Sham-EA, blank control) EA was observed to have a statistically significant improvement when compared with acupoint gut embedding, sham-EA, and acupuncture with sham-EA based on the VAS score ( p < 0.05) EA is an effective treatment for reducing migraine duration when compared with other forms of therapy; however, the lack of differences in adverse effects warrants further study Zhang et al (2019) [ 39 ] 15 Systematic reviews Studies showed acupuncture to be more effective than drug therapy, sham acupuncture, and traditional Chinese m Acupuncture has been reported to be useful in reducing migraine frequency, duration, and VAS score, which positions it to be a helpful treatment for prevention and management; however, the subjectivity of outcomes measures and low sample sizes highlight the need for more high-quality studies Chen et al (2020) [ 41 ] 19 RCTs ( n = 3656) Indirect comparison analyses show that acupuncture has advantages over propranolol in reducing migraine frequency, number of episodes, and adverse effects Acupuncture may be considered to be a first-line agent for migraine prophylaxis someday given the preliminary data here showing its effectiveness and safety when compared to propranolol Allais et al (2019) [ 45 ] Single-cohort study of EAP one session every 3 weeks for patients with chronic migraines ( n = 20 women) <...>…”
Section: Evidence For Acupuncturementioning
confidence: 99%